The prodrome of migraine: mechanistic insights and emerging therapeutic strategies - Gao, Linli; Zhao, Fangling; Tu, Yujie; Liu, Kaiming (Frontiers in Neurology, 2024)
Migraine is a common clinical chronic neurovascular disease characterized by recurrent, mostly unilateral, moderate or severe, pulsatile headache. It can be divided into four clinical stages: premonitory (prodrome), aura, headache and postdrome. The early warning value of the prodrome in migraine has been largely verified in various studies. In fact, the prodrome of migraine has received increasing attention as it can serve as an ideal therapeutic window for early intervention and effective treatment of migraine. In recent years, the pathophysiological and molecular biological mechanisms in the prodromal stage of migraine have been extensively studied, and great progress has been made in understanding the disease. This review paper aims to provide an overview of recent studies mainly focused on the prodrome of migraine, discuss the biological mechanisms underlying the clinical profile, and reveal novel therapeutic strategies for preventing or blocking migraine onset during its prodrome.